2019
DOI: 10.1542/peds.2018-3955
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Earnings of Early- and Midcareer Pediatricians

Abstract: BACKGROUND: The US physician workforce includes an increasing number of women, with pediatrics having the highest percentage. In recent research on physicians, it is indicated that men earn more than women. It is unclear how this finding extends to pediatricians. METHODS: We examined cross-sectional 2016 data on earnings from the American Academy of Pediatrics Pediatrician Life and Career Experience Study, a longitudinal study of early-and midcareer pediatricians. To estimate adjusted differences in pediatrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 35 publications
(56 reference statements)
1
42
0
Order By: Relevance
“…49 National studies and surveys, however, consistently report pay gaps for women in pediatrics even after adjusting for confounding variables. 6,50,51,[53][54][55][56][57] For example, Medscape and Doximity ranked pediatrics among the lowestcompensated medical specialties,…”
Section: Disparities In Equity Diversity and Inclusion For Women Inmentioning
confidence: 99%
See 1 more Smart Citation
“…49 National studies and surveys, however, consistently report pay gaps for women in pediatrics even after adjusting for confounding variables. 6,50,51,[53][54][55][56][57] For example, Medscape and Doximity ranked pediatrics among the lowestcompensated medical specialties,…”
Section: Disparities In Equity Diversity and Inclusion For Women Inmentioning
confidence: 99%
“…25,29,59 To better understand the effects of pay disparities, we calculated the potential investment yield from the gaps found in 2 compensation studies demonstrating genderrelated disparities in pediatrics even after accounting for confounding variables. Jena et al 51 reported the annual gender-related pediatric compensation gap was ∼$24 500, whereas Frintner et al 54 more recently found the gap to be $8000.…”
Section: Figurementioning
confidence: 99%
“…Even those specialties in which women predominate (ie, pediatrics and family practice) are not protected from salary disparities. 4,5 Salary data from 998 pediatricians (27.5% men, 72.5% women) who worked in general pediatrics, hospitalist care, or subspecialty care showed that women earned 76% of what men earned ($51,000 average annual shortfall), before adjustment for labor force characteristics such as demographics, work hours, and subspecialty. After adjustment, women earned 87% to 94% of what men earned ($8,000 to $26,000 annual shortfall).…”
Section: "Wmentioning
confidence: 99%
“…After adjustment, women earned 87% to 94% of what men earned ($8,000 to $26,000 annual shortfall). 4 Other approaches to address the potential for gender-based wage gaps include structured compensation models based on rank and time-in-rank in a given subspecialty. A compensation model developed by the Department of Pediatrics at Cincinnati Children's Hospital Medical Center (710 full-time faculty, 47% women) in 2015 is not based on individual productivity (eg, relative value units) but rather is tied directly to nationwide standards of compensation from the Association of Academic Administrators in Pediatrics (AAAP), which tabulates annual salary data from approximately 100 academic pediatric departments and provides both national and regional data at the 25 th , 50 th , and 75 th percentiles by rank (instructors, assistant professors, associate professors, and professors) in each subspecialty.…”
Section: "Wmentioning
confidence: 99%
“…5 Furthermore, gender or maternal bias negatively affects individuals in medicine in regards to future employment, career advancement, and compensation. [6][7][8][9][10][11] Given these implications, we celebrate the removal of the practice interruptions criterion as it was unintentionally biased against women. Eligibility criteria that considered practice interruptions would have disproportionately affected women due to leaves related to pregnancy and due to discrepancies in the length of parental leave for mothers versus fathers.…”
mentioning
confidence: 99%